2013
DOI: 10.1158/1055-9965.epi-13-0446
|View full text |Cite
|
Sign up to set email alerts
|

Postdiagnosis Cruciferous Vegetable Consumption and Breast Cancer Outcomes: A Report from the After Breast Cancer Pooling Project

Abstract: Cruciferous vegetables are a major source of glucosinolate-derived bioactive compounds such as isothiocyanates, which have been shown in animal and in vitro studies to inhibit cancer growth and progression. Few studies have investigated cruciferous vegetable intake after diagnosis and breast cancer outcomes. Using data from the After Breast Cancer Pooling Project, which includes prospective data from US and Chinese breast cancer survivors, we evaluated the association of cruciferous vegetables with breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 21 publications
(35 reference statements)
0
35
0
Order By: Relevance
“…The protective effect reached a significant 35% decrease in women on adjuvant tamoxifen therapy. A pooling of 4 cohorts of women with stages I-III breast cancer by Nechuta et al 11 showed no significant associations between intake of cruciferous vegetables and breast cancer recurrence or total mortality after a median follow-up of 9 years. In addition to variations in intake across studies, particularly within the highest quartiles, measurement errors in dietary assessment limit the interpretation of the epidemiological evidence.…”
Section: Epidemiological Evidencementioning
confidence: 97%
See 2 more Smart Citations
“…The protective effect reached a significant 35% decrease in women on adjuvant tamoxifen therapy. A pooling of 4 cohorts of women with stages I-III breast cancer by Nechuta et al 11 showed no significant associations between intake of cruciferous vegetables and breast cancer recurrence or total mortality after a median follow-up of 9 years. In addition to variations in intake across studies, particularly within the highest quartiles, measurement errors in dietary assessment limit the interpretation of the epidemiological evidence.…”
Section: Epidemiological Evidencementioning
confidence: 97%
“…Overall, point estimates of the odds ratio and relative risk suggest a protective role, though less so in US studies. 1,3,4,9 This may be due to the overall lower intakes in the United States, 11 particularly in comparison with intakes in Asian countries, where the risk of breast cancer is lower among those with greater intakes. 5,7,8 A recent meta-analysis of 13 case-control and prospective cohort studies and 18 673 individual cases suggested that overall high intake of cruciferous vegetables was significantly associated with a 15% lower risk of breast cancer.…”
Section: Epidemiological Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Although none of these studies provide a direct correlation between cancer incidence and intake of a specific ITC, many studies do identify a correlation between the total ITC intake in the form of cruciferous vegetables and reduced risk of several types of cancers in lung, breast, gastric, bladder, colorectal, pancreatic, prostate and kidney (Table 1) [5, 827]. Interestingly, there are also few studies where the results obtained were opposite to the preventive effects of cruciferous vegetables.…”
Section: Epidemiological Evidence For Chemo-preventive Effects Of mentioning
confidence: 99%
“…One study of breast cancer showed improved survival associated with a greater variety in consumption of vegetables and fruit and of fruit alone (75) and one showed reduced recurrence with higher intake of vegetables (76). A third breast cancer study showed no association between survival or recurrence and intake of cruciferous vegetables (77). One study of prostate cancer showed reduced likelihood of progression associated with higher intake of cruciferous vegetables (78).…”
Section: Plant Foods and Cancermentioning
confidence: 99%